2020
DOI: 10.3389/fmars.2020.00208
|View full text |Cite
|
Sign up to set email alerts
|

Migration Corridors and Threats in the Gulf of Mexico and Florida Straits for Loggerhead Sea Turtles

Abstract: Along migration corridors, animals can face natural and anthropogenic threats that differ from those in breeding and non-breeding residence areas. Satellite telemetry can aid in describing the timing and location of these migrations. We use this tool with switching state-space modeling and line kernel density estimates to identify migration corridors of post-nesting adult female loggerhead sea turtles (Caretta caretta, n = 89 tracks) that nested at five beaches in the Gulf of Mexico. Turtles migrated in both n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 46 publications
3
21
0
Order By: Relevance
“…We used switching state space modeling (SSM) to characterize the movements of tagged turtles. The model was previously described in Jonsen et al (2005) and has been applied to model movement of many marine animals (Bailey et al, 2009;Shillinger et al, 2010;Maxwell et al, 2011;Shaver et al, 2016;Iverson et al, 2020). Specifically, we applied a Bayesian hierarchical movement model with behavioral-state switching in the R package "bsam" (Jonsen et al, 2005(Jonsen et al, , 2017Jonsen, 2016;R Core Team, 2020) by calling JAGS (package rjags; Plummer, 2019) to run the Markov Chain Monte Carlo (MCMC) algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…We used switching state space modeling (SSM) to characterize the movements of tagged turtles. The model was previously described in Jonsen et al (2005) and has been applied to model movement of many marine animals (Bailey et al, 2009;Shillinger et al, 2010;Maxwell et al, 2011;Shaver et al, 2016;Iverson et al, 2020). Specifically, we applied a Bayesian hierarchical movement model with behavioral-state switching in the R package "bsam" (Jonsen et al, 2005(Jonsen et al, , 2017Jonsen, 2016;R Core Team, 2020) by calling JAGS (package rjags; Plummer, 2019) to run the Markov Chain Monte Carlo (MCMC) algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…The southern portion of the Atlas study area, near the Florida Keys, was identified as a high-use migratory corridor for Loggerheads, Greens, and Hawksbills based on a review of previous satellite telemetry studies (Foley et al 2013; Shaver et al 2016; Iverson et al 2020; Hart et al 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Insufficient data were available on hawksbill turtles to identify HUAs using these methods. The southern portion of the Atlas study area, near the Florida Keys, was identified as a high-use migratory corridor for loggerheads, greens, and hawksbills (Fig 5) based on a review of previous satellite telemetry studies [37,[53][54][55]. The union of HUA and migratory corridor layers for leatherback, Kemp's ridley, hawksbill, loggerhead, and green sea turtles were scored at 0.1, 0.2, 0.2, 0.4, and 0.5, respectively.…”
Section: Plos Onementioning
confidence: 99%